Pembangunan Green Belt Sebagai Antisipasi Pencemaran Udara Industri Pupuk Di Kalimantan Timur - Susanto, Joko Prayitno; Komarawidjaja, Wage (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2018)
ABSTRACTThe fertilizer industry based on their environmental concerned in East Kalimantan is committed to protecting environmental sustainability and biodiversity which one of its efforts is to reduce the impact of air pollution by building Green Belt that serves as a buffer zone. The main element of the green belt is the vegetation that naturally acts as an atmospheric purifier by absorbing gaseous and particulate pollutants through its leaves. Green Belt Vegetation, with leafy and coarse leaf surfaces, with wide leaves, dense canopy with tight leaves expected to reduce air pollutant concentration from the fertilizer industry to surrounding residential areas. Thus the Green Belt will be built to help overcome the problem of air pollution impact in the settlement area around industrial area. sengon and teak.Keywords: Green belt, fertilizer industry, air pollution, dust, particulates.ABSTRAKIndustri pupuk ini bermaksud membangun proses industri pupuk yang ramah lingkungan untuk melindungi lingkungan dan keanekearagaman hayati dariÃ‚Â pencemaran udara dengan membangun daerah penyangga dikenal sebagai sabuk hijau (Green Belt). Unsur utama sabuk hijau adalah vegetasi yang secara alamiah berfungsi sebagai pembersih atmosfir dengan menyerap polutan berupa gas dan partikel melalui daunnya. Ã‚Â Ã‚Â Vegetasi Green Belt, dengan permukaan daun berbulu dan kasar, dengan daun lebar, tajuk yang rapat dengan daun yang rapat diharapkan mampu mengurangi konsentrasi pencemar udara dari industri pupuk menuju areal permukiman disekitarnya. Dengan demikian Green Belt Ã‚Â yang dibangun akan dapat membantu mengatasi masalah dampak pencemaran udara diareal permukiman sekitar kawasan industri.Kata kunci: Sabuk hijau (green belt), industri pupuk, pencemaran udara, debu, partikulat.